Legal Problems in Proving the Crime of Claiming Supernatural Powers under Article 252 of the Indonesian Criminal Code - Tumbur Tumbur; Rahmat Ramadhani (Abdurrauf Law and Sharia, 2026)
The enactment of Article 252 of Law Number 1 of 2023 concerning the Indonesian Criminal Code introduces a unique criminal offence relating to claims of supernatural powers, raising significant legal issues concerning its enforcement within Indonesia's criminal justice system. This study examines the legal construction of Article 252 and analyzes the evidentiary framework required to establish criminal liability for offences involving supernatural claims. The research employs a normative juridical method using statutory, conceptual, and doctrinal approaches. Primary legal materials include the 1945 Constitution, Law Number 1 of 2023 concerning the Criminal Code, Law Number 8 of 1981 concerning the Criminal Procedure Code, and related legislation, while secondary legal materials comprise legal doctrines, scholarly books, and peer-reviewed journal articles. The collected materials were analyzed through grammatical, systematic, and teleological interpretation using deductive legal reasoning. The findings indicate that Article 252 constitutes a formal offence, whereby criminal liability is established by proving the prohibited conduct rather than the actual existence or effectiveness of supernatural powers. Accordingly, the object of proof should focus on the defendant's conduct, intent, and legally admissible evidence instead of metaphysical claims. This study also identifies a normative gap resulting from the absence of explicit evidentiary standards under Article 252. Its novelty lies in proposing a doctrinal evidentiary model that emphasizes objectively verifiable conduct, thereby strengthening the compatibility of Article 252 with the principles of legality, legal certainty, due process of law, and modern criminal evidence. [Pemberlakuan Pasal 252 Undang-Undang Nomor 1 Tahun 2023 tentang KUHP Indonesia memperkenalkan tindak pidana unik yang berkaitan dengan klaim kekuatan supranatural, sehingga menimbulkan isu hukum yang signifikan terkait penegakannya dalam sistem peradilan pidana Indonesia. Studi ini meneliti konstruksi hukum Pasal 252 dan menganalisis kerangka pembuktian yang diperlukan untuk menetapkan tanggung jawab pidana atas tindak pidana yang melibatkan klaim kekuatan supranatural. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan hukum, konseptual, dan doktrinal. Materi hukum primer meliputi Konstitusi 1945, Undang-Undang Nomor 1 Tahun 2023 tentang KUHP, Undang-Undang Nomor 8 Tahun 1981 tentang KUHP, dan peraturan perundang-undangan terkait, sedangkan materi hukum sekunder terdiri dari doktrin hukum, buku-buku ilmiah, dan artikel jurnal ilmiah. Materi yang dikumpulkan dianalisis melalui interpretasi gramatikal, sistematis, dan teleologis menggunakan penalaran hukum deduktif. Hasil penelitian menunjukkan bahwa Pasal 252 merupakan tindak pidana formal, di mana tanggung jawab pidana ditetapkan dengan membuktikan perbuatan yang dilarang, bukan keberadaan atau keefektifan kekuatan supranatural yang sebenarnya. Oleh karena itu, objek pembuktian harus berfokus pada perilaku, niat, dan bukti yang sah secara hukum dari terdakwa, bukan pada klaim metafisik. Studi ini juga mengidentifikasi kesenjangan normatif yang timbul dari tidak adanya standar pembuktian eksplisit berdasarkan Pasal 252. Kebaruannya terletak pada pengusulan model pembuktian doktrinal yang menekankan perilaku yang dapat diverifikasi secara objektif, sehingga memperkuat kesesuaian Pasal 252 dengan prinsip-prinsip legalitas, kepastian hukum, proses hukum yang adil, dan bukti pidana modern.]